CD44 and CLDN3 as immune-metabolic regulators in acute pancreatitis: a multi-modal transcriptomics study and experimental validation - Wang, Xinwei; Hu, Cheng; Liu, Tian; Yang, Rui; Shen, Yuxin; Zhang, Shihang; Deng, Lihui; Xia, Qing (Frontiers in Immunology, 2025)
Acute pancreatitis (AP) is an inflammatory disorder of exocrine pancreas regulated by a complex interaction between injured pancreatic acinar cells and immune cells. Recent studies indicated the crucial role of glycolysis in regulating immune cell function and inflammation. Here, we identified 43 glycolysis-related differentially expressed genes (DEGs) from transcriptomic datasets (GSE65146 and GSE109227). Through three machine learning algorithms,Claudin-3 (CLDN3) and CD44 were identified as key glycolysis-related DEGs. Their significant upregulation was further validated in an independent dataset. Then, single-sample gene set enrichment analysis revealed CLDN3 and CD44 were significantly correlated with immune-related structural remodeling and immune infiltration patterns. Single-cell RNA-seq analysis from GSE279876 confirmed that CLDN3 was downregulated in acinar cells, while CD44 was enriched in ductal and immune cells. To validate these findings, we established an AP model by 10 hourly intraperitoneal injections of caerulein (100 μg/kg) combined with one injection of lipopolysaccharide (10mg/kg). We confirmed that CD44 was upregulated and primarily expressed in inflammatory cells in AP mice. Interestingly, while CLDN3 mRNA levels were increased, its protein expression was reduced. Immunohistochemistry further revealed a redistribution of CLDN3 from the apical membrane to the cytoplasm in the pancreas of AP mice. Our findings, for the first time, indicated that CD44 and CLDN3 were crucial biomarkers associated with immune-metabolic dysregulation between pancreatic acinar cells and immune cells. The results of this study showed the potential of these two biomarkers as therapeutic targets for AP.